DIVERSITY OF BIRD SPECIES IN THE FAONG RESORT SASARATA COASTAL MANGROVE FOREST AREA, NORTH SERAM DISTRICT - June S. Amanukuany; Fanny Soselisa; A. Tuhumury (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
This study aims to determine the diversity of bird species in the coastal mangrove area of ​​Faong Resort Sasarata, North Seram District. The data collection method in this study used the IPA (Indices Ponctuele d'Abundance) method. The results of this study indicate that at the research site 301 birds were found with a total of 8 species of bird species, namely the Sea Pergam (Ducula bicolor), Garden Fan (Rhipidura leucophrys), Sungai Cekakak (Todiramphus chloris), White Eye Pergam (Ducula perspicillata), Gray Brush (Myiagra galeata) Seram Cikukua (Philemon subcorniculatus), Seram Cikukua (Philemon subcorniculatus), Australian Ibis (Thareskiornis molucca), Rainbow Lorikeet (Trichoglossus haematodus). The index value of the diversity of bird species (H') is 1.954 which is in the medium level category. The habitat of bird species on the coast of Faong Beach is quite stable.